HDAC Inhibitor Sodium Butyrate Augments the MEF2C Enhancement of Nampt Expression under Hypoxia - Yan, Shao-Fei; You, Hong-Jie; Xing, Tian-Yu; Zhang, Chen-Guang; Ding, Wei (Current Pharmaceutical Design, 2014)
Nicotinamide phosphoribosyl transferase (Nampt) is the rate-limiting enzyme for the salvage biosynthesis of nicotinamide adenine dinucleotide (NAD). Although elevated level of Nampt expression has been observed in various cancers, the involvement of Nampt promoter regulation was not well understood. We have identified a cluster of MEF2 recognition sites upstream of the functional hypoxia response elements (HREs) within the human Nampt promoter, and demonstrated that the two MEF2 sites at -1272 and -1200 were functional to upregulate the promoter activity by luciferase reporter assays. The Nampt promoter was able to be activated cooperatively following hypoxic stimulation by CoCl2 treatment with associated MEF2C overexpression. During the investigation on MEF2C regulation of endogenous Nampt expression in HeLa cells, the most significant enhancement of Nampt expression observed was by overexpression of MEF2C in combination with sodium butyrate exposure. By chromatin immunoprecipitation with a MEF2C anti-body, we found that MEF2C indeed interacted with endogenous Nampt promoter. The requirement of HDAC inhibition for the MEF2C enhancement of Nampt transcription was verified by RNAi of HDAC. Our results were in support of reports indicating that MEF2 family transcription factors interacted with HDACs and regulated downstream gene expression at the epigenetic levels. Our study provided important evidence to demonstrate the sophisticated mechanism of endogenous Nampt promoter regulation, and therefore, will help to better understand the Nampt overexpression in cancer progression, especially in the context of MEF2C upregulation which frequently occurred in cancer development and drug resistance.
Keywords: MEF2C